2019
DOI: 10.1021/acs.chemmater.8b05020
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polyacrylic Acid (PAA) Binder on the Solid Electrolyte Interphase in Silicon Anodes

Abstract: To obtain high-energy density Li-ion batteries for the nextgeneration storage devices, silicon anodes provide a viable option because of their high theoretical capacity, low operating potential versus lithium (Li), and environmental abundance. However, the silicon electrode suffers from large volume expansion (∼300%) that leads to mechanical failure, cracks in the SEI (solid electrolyte interphase), and loss of contact with the current collector, all of which severely impede the capacity retention. In this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 46 publications
1
107
0
1
Order By: Relevance
“…The cycling behavior of the electrodes unambiguously demonstrated the importance of the pH during processing of the anodes fabricated from microcrystalline Si and PAA. While the benefits of the low processing pH for some types of Si are well documented 27 , for the microcrystalline Si used in the present work the effect is dramatic. Specifically, slurry processing at neutral pH leads to largely non-functioning anode where complete capacity fading occurs after completion of formation cycles.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The cycling behavior of the electrodes unambiguously demonstrated the importance of the pH during processing of the anodes fabricated from microcrystalline Si and PAA. While the benefits of the low processing pH for some types of Si are well documented 27 , for the microcrystalline Si used in the present work the effect is dramatic. Specifically, slurry processing at neutral pH leads to largely non-functioning anode where complete capacity fading occurs after completion of formation cycles.…”
Section: Resultsmentioning
confidence: 71%
“…It has been shown that treatment of PAA with LiOH/NaOH (at pH around 8) allows to reduce irreversible capacity 26 . PAA has been found to have better capacity retention compared to CMC when LiFSI salt was used for electrolyte formulation 27 . The performance of binder system also strongly depends on the selection of the silicon material and selected electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Commercialization of silicon‐based lithium‐ion batteries requires favorable stability of the battery. However, the large volume expansion of the silicon electrode can cause the SEI layer to break and lose electrical contact with the current collector . Designing a stable electrode structure is an effective method to improve the large volume change of the Si anode during charging/discharging of LIBs .…”
Section: Selection Of Electrolyte For Silicon Anodementioning
confidence: 99%
“…However, they are incompatible with silicon electrodes and are unable to maintain the integrity of the silicon electrodes during cycling . As shown in Figure , Polyacrylic acid(PAA) binders showed greater capacity retention compared to CMC . The anode prepared by PAA as a binder for silicon nanoparticles showed a capacity loss of only 8% in 300 cycles .…”
Section: Selection Of Electrolyte For Silicon Anodementioning
confidence: 99%
See 1 more Smart Citation